Biodiesel production from waste cooking oil by immobilized lipase on superparamagnetic Fe3O4 hollow sub-microspheres. Issue 6 (1st November 2016) - Liu, Changxia; Yuan, Jinlei; Gao, Huafeng; Liu, Chunqiao
Abstract: Superparamagnetic Fe3 O4 hollow sub-microspheres (FHSM) with strong response to an external magnet were prepared via a solvothermal method, followed by acid etching. Lipase from Candida sp. 99–125 was directly immobilized onto the amino-functional FHSM by simple adsorption, without glutaraldehyde linkage. The immobilized lipase was used to catalyze the esterification/transesterification of waste cooking oil with methanol to produce fatty acid methyl ester (FAME), a major source of biodiesel. FAME yield exceeded 93.4% over a wide range of temperatures from 10 to 40 °C. Notably, stability was clearly improved at the lower temperatures, in particular, giving a FAME yield of 89.6% after eight cycles of use at 10 °C.